2021
DOI: 10.1186/s43168-021-00071-0
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function before and after surgical correction of scoliosis

Abstract: Background As one of the restrictive lung diseases, scoliosis can be treated by surgical intervention to enhance the pulmonary function of that group of patients. The purpose of the study was to determine the effects of scoliosis correction on pulmonary function after a 6-month duration. Around 30 patients with scoliosis were aged between 10 and 40 years old subjecting to posterior spinal fusion surgery who had been enrolled in the study; all of them were subjected to Cobb’s angle measuring and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Rahma et al [24] found that the mean preoperative Cobb angle was 96.75 ± 20.59 and this was corrected to 80.69 ± 20.36 with a flexibility index of 16%. Ahmed et al [27] found that the mean Cobb angle of thoracic curve was 59° for all patients submitted to thoracotomy with anterior or posterior arthrodesis, which showed a significant decrease after surgery to 39°, with a correction rate of about 31%. Data collected from other series using the combined approach revealed that in the Bullmann et al [28] series [combined], the preoperative Cobb angle of the curve was 93.4 ± 12.2 [range: 80-122] and corrected to 72.1 ± 17.1 [range: 48-118] on bending films [flexibility is 23%].…”
Section: Discussionmentioning
confidence: 99%
“…Rahma et al [24] found that the mean preoperative Cobb angle was 96.75 ± 20.59 and this was corrected to 80.69 ± 20.36 with a flexibility index of 16%. Ahmed et al [27] found that the mean Cobb angle of thoracic curve was 59° for all patients submitted to thoracotomy with anterior or posterior arthrodesis, which showed a significant decrease after surgery to 39°, with a correction rate of about 31%. Data collected from other series using the combined approach revealed that in the Bullmann et al [28] series [combined], the preoperative Cobb angle of the curve was 93.4 ± 12.2 [range: 80-122] and corrected to 72.1 ± 17.1 [range: 48-118] on bending films [flexibility is 23%].…”
Section: Discussionmentioning
confidence: 99%
“…The manipulation of thoracic structures and potential effects on lung function necessitates careful monitoring of respiratory parameters during surgery. Postoperative respiratory care is basic to prevent complications such as atelectasis and pneumonia [77]. Scoliosis can negatively influence the circulatory, digestive, endocrine, integumentary, lymphatic, muscular, nervous, and respiratory systems.…”
Section: Risk Of Respiratory Infectionsmentioning
confidence: 99%
“…Ovdje također treba napomenuti da usprkos sve sofisticiranijem operativnom pristupu, koji uspijeva značajno korigirati stupanj deformiteta, prema podat cima iz literature još uvijek ne bilježimo očekivani oporavak plućne funkcije nakon operativnog zahvata, pogotovo kod starijih bolesnika. 13,22,35,36,37 Konačno, odluku o respiratornoj potpori u vidu ne invazivne ili invazivne mehaničke ventilacije donosi mo na temelju djetetovog kliničkog stanja, procjene plućne fukcije, nalaza acidobaznog statusa, kapnome trije i oksimetrije te nalaza polisomnografije.…”
Section: Pulmološko Praćenje Bolesnika S Rizikom Od Razvoja Respirato...unclassified